2017
DOI: 10.1186/s12989-016-0182-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biological responses to nanofibrillated cellulose by human dermal, lung and immune cells: surface chemistry aspect

Abstract: BackgroundNanocellulose, and particularly nanofibrillated cellulose (NFC), has been proposed for a diversity of applications in industry and in the biomedical field. Its unique physicochemical and structural features distinguish nanocellulose from traditional materials and enable its use as an advance nanomaterial. However, its nanoscale features may induce unknown biological responses. Limited studies with NFC are available and the biological impacts of its use have not been thoroughly explored. This study as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
149
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(176 citation statements)
references
References 42 publications
18
149
1
1
Order By: Relevance
“…This hydrogel is easy to handle and is biocompatible with human cells, whilst also allowing the simple retrieval of cells from the scaffold for further use [25,26]. Although the immunogenicity of plant-derived NFC is still under investigation, the low immune response to other plant derived hydrogels has been reported [27] [12,28].…”
Section: Discussionmentioning
confidence: 99%
“…This hydrogel is easy to handle and is biocompatible with human cells, whilst also allowing the simple retrieval of cells from the scaffold for further use [25,26]. Although the immunogenicity of plant-derived NFC is still under investigation, the low immune response to other plant derived hydrogels has been reported [27] [12,28].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to CNC, the NCF used in this study has been found to be more cytotoxic to human A549 cells (24 or 72 h post exposure) (Menas et al 2017) and in mice (24 h post-exposure) (Yanamala et al 2014). Other studies of different NCF types reported low cytotoxicity but robust inflammatory cytokine/chemokine production in dermal fibroblasts, lung MRC-5 cells, and THP-1 macrophages (Bhattacharya et al 2017;Lopes et al 2017). The present data indicate that by Day 14, NCF-treated mice exhibited an immune microenvironment favoring differentiation of T-cells toward a T H 1-phenotype (more obviously seen in highdose exposure group), as revealed by increased APC activation, maturation, and enhanced secretion of IL-12p70, MCP-1, MIP-1a, and GM-CSF (Colantonio et al 2002;Zhang et al 2014).…”
Section: Discussionmentioning
confidence: 73%
“…Fiber toxicity is driven by high aspect ratio with high strength and long retention times, and there is always concern for the induction of ASB-like pathogenicity for each emerging material or application. In the case of nanoscale fibers, additional variables are added that might complicate the established pathogenicity mechanisms due to uncertain biological fate and biocompatibility (Allegri et al 2016;Lopes et al 2017). The goal of the current study was to determine whether fibrillary nanocellulose, despite having the same chemical composition as the crystalline form, elicits different local and systemic subacute immune responses upon pulmonary exposure in a mouse model of bolus pharyngeal aspiration, and second, if the response would be closer to the one produced by micro-sized crocidolite fibers or CNTs.…”
Section: Discussionmentioning
confidence: 99%
“…by functionalizing it with specific chemical groups or by endowing it with an electrical charge. Wood-derived nanofibrillated cellulose (NFC) modified with carboxymethyl and hydroxypropyltrimethylammonium groups elicited a lower pro-inflammatory effect than unmodified NFC in human dermal fibroblasts, in lung MRC-5 cells and in human macrophage-like THP-1 cells [273]. Anionic NFC films significantly activated THP-1 cells towards a pro-inflammatory phenotype, whereas cationic and unmodified cellulose induced only mild activation of these cells [274].…”
Section: Potential Cytotoxicity and Immunogenicity Of Nanocellulosementioning
confidence: 99%